Estimating Street Dog Populations and Enhancing Rabies Surveillance in Bruhat Bengaluru Mahanagara Palike, Karnataka, India: A Single-Sight and Sight-Resight Approach - Raaga R.; Suresh K. P.; Divakar Hemadri; Baldev Raj Gulati; Chandraiah T.; Balaji Chandrashekar; Ravi Kumar K. P.; Manjunath Shinde. S. M.; Shrikrishna Isloor; Asha G. K.; et al. (Scientific Research, New Technologies and Applications Vol. 10, 2024)
Background: Rabies, a lethal viral disease, poses a significant public health threat globally. Transmitted through the saliva of infected animals, particularly through bites, the rabies virus targets the nervous system, leading to severe neurological symptoms. Aim: The study aims to estimate Bengaluru’s street dog population and assess the effectiveness of interventions for population control and public health, with a particular focus on rabies management. It also seeks to develop a blueprint for responsible urban management that prioritizes compassion and safety for both humans and street dogs. Study Design and Methodology: This study utilizes the Bruhat Bengaluru Mahanagara Palike (BBMP) street dog survey to estimate the street dog population in Bengaluru. It applies Single-Sight and Sight-Resight methods, using the Lincoln-Petersen Formula and Chapman’s Correction for accuracy. The population is categorized by zones, providing nuanced insights to guide targeted interventions based on factors like sex, age composition, and neutering status. For the first six days, a single-sight survey was conducted by pairs of surveyors on two-wheelers who traversed every road in their assigned zone, photographing and recording observed dogs. Over the following six days, all sighted dogs were documented again, regardless of prior observation. Results: The results reveal significant variations in the street dog population across different zones of Bengaluru, shedding light on the diverse challenges and characteristics of these communities. The study estimates Bengaluru’s street dog population at approximately 279,335, showing a 10% reduction from the 2019 estimate of 309,898, which suggests effective intervention measures. Additionally, there has been a notable increase in neutering rates, rising from 51.16% in 2019 to 71.85% in this study, underscoring the importance of continued population control efforts for public health, especially in rabies prevention. Conclusion: The observed reduction in street dog population is crucial for controlling disease transmission and enhancing public safety. The study aims to offer a blueprint for responsible urban management that emphasizes compassion and safety for humans and street dogs alike. By showcasing the success of evidence-driven policies and collective efforts, it seeks to set a standard for sustainable urban practices that promote harmonious coexistence between communities and street dogs. Continued collaboration and informed decision-making are recommended to foster a safer and more compassionate environment for all residents of Bengaluru.